Painting place: Re-imagining landscapes for older people's subjective wellbeing. (July 2016) - Rose, Emma; Lonsdale, Stephen
Abstract: This study provides insights into how a participatory painting activity impacts older people's subjective wellbeing. The study uses qualitative methods to analyze the findings, and employs qualitative data collection methods to examine how creativity conducted in an environment of relational connectivity is beneficial to wellbeing. The findings demonstrate that processes of re-imagining landscape contribute to participants' retaining significant places in the mind when physical engagement is limited. The study reveals how the activity of re-imagining landscape provokes emotions and memories that help participants connect the past with the present, and to connect their older and younger-age selves, positively to reaffirm their older age identity. The paper reflects on the intervention as a form of encounter with landscape whose benefits are potentially therapeutic for different groups, particularly those for whom engagement with memories may assist with processes of adaptation or transition. Highlights: Insights into how participatory painting impacts older people's wellbeing. Re-imagining landscape and retaining significant life spaces in the mind. Painting, connectivity, identity and attachment to place. The therapeutics of relational aesthetics. Therapeutic benefits assist with processes of adaptation or transition.